Correlation between AMH and Polycystic Ovarian Syndrome Phenotypes among Iraqi Population - Fatin Shallal Farhan (Journal of Global Pharma Technology, 2019)
Background: Anti-Mullerian hormone is considered as a marker with has an important function in ovarian folliculogenesis besides the steroidogenesis. Anti-mullerian hormone with ovarian stimulation may guide the treatment plan in infertility. Objective:  To evaluate the anti-Mullerian hormone role in identification and diagnosis of polycystic ovarian syndrome phenotypes in Iraqi population. Patients and Methods: This retrospective cohort study was carried at Al-Yarmuk Teaching Hospital in Baghdad from the 1st January 2016 to the 1st of December 2018. Ninety-nine women were enrolled in the study. Anti-Mullerian hormone was obtained from those women, those who had high AMH above 5 ng/ml were enrolled in the study, then they classified based on the level of AMH into three groups: First group, their AMH 5-10 ng/ml, the second group, the AMH level was 10-14 ng/ml, the third group their AMH was more than 14 ng /ml. Then the comparison between these groups was done according to their polycystic ovary syndrome phenotype, and their endocrine parameters. Results: The percentages of Hyperandrogenimia were not statistically significant except for that between group 3 and 2 (78.8% vs. 50% respectively; the P value was= 0.014). The polycystic ovaries by ultrasound was significantly higher in group 3 (as the P value was= 0.001). PCOS diagnosis was significantly more prevalent in group 2 (91.2%) and group 3 (100%) in comparison with group 1 (50%). The difference  was statistically significant for women with polycystic ovary syndrome who had  regular period and the percentages were (65.6% vs. 26.5% vs. 3% for group 1 vs. 2 and 3 respectively )while there was a significant higher percentages for  oligomenorrrhea in group 2 (67.6%) ,and group 1 (31.3%), Whereas proportion of amenorrhea was significantly higher  in group 2 (5.9%) , and group 3 (24.2%) in comparisons to  group 1 (3.1%). Conclusion: Antimullerian hormone levels might be used for polycystic ovary syndrome diagnosis and determine its severity. The majority of women with Antimullerian hormone >10 ng/mL will have severe type of PCOS.Keywords: (PCOS), Antimullerian hormone, Polycystic phenotype.